2018
DOI: 10.1016/j.prnil.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prostatic inflammation on clinical outcomes in patients with benign prostate hyperplasia

Abstract: BackgroundTo investigate the effect of asymptomatic inflammatory prostatitis on clinical outcomes of patients undergoing trans urethral resection of prostate due to benign prostatic hyperplasia.Materials and methodsA total of 514 patients were enrolled in the study. Clinical parameters and pathological results were compared before and one year after surgery.ResultsOf the patients 310 were diagnosed with purely benign prostatic hyperplasia and the others were diagnosed with both prostatic inflamation (cathegory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
2
14
0
5
Order By: Relevance
“…Despite the variation in prostate size reduction after intervention between the 3 groups, IPSS score improvement was nearly similar in all groups; this may be due to asymptomatic prostatic inflammation that affects the LUTSs as mentioned by Cakir et al. 12 In addition, the subjectivity of IPSS score and patient to patient variability and the different education level as mentioned by Taneja et al 13 2017, that education level may be affected and the visual prostate symptom score would be more appropriate in comparison to IPSS.…”
Section: Discussionmentioning
confidence: 68%
“…Despite the variation in prostate size reduction after intervention between the 3 groups, IPSS score improvement was nearly similar in all groups; this may be due to asymptomatic prostatic inflammation that affects the LUTSs as mentioned by Cakir et al. 12 In addition, the subjectivity of IPSS score and patient to patient variability and the different education level as mentioned by Taneja et al 13 2017, that education level may be affected and the visual prostate symptom score would be more appropriate in comparison to IPSS.…”
Section: Discussionmentioning
confidence: 68%
“…This finding suggested that periodontal scaling should be covered in routine healthcare for old males and that BPH therapy should be accompanied by periodontal treatment. In addition, asymptomatic prostate inflammation can worsen lower urinary tract symptoms and urinary flow rate in patients with BPH [41], while periodontal treatment can effectively reduce such risks. Additionally, basic laboratory studies have demonstrated that infections by periodontal pathogens can accelerate some systemic conditions by inciting inflammatory responses and further affecting apoptosis, and the mechanisms have been corroborated in atheroma deposition [42], preterm low birth weight among infants [43], cognitive decline [44] and respiratory infection [45] but not in BPH until now.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 428 TURP specimens showed that those with evidence of chronic prostatitis had a significantly higher preoperative IPSS (29.9 vs 23). Despite addressing their outlet obstruction, they had worse outcomes at 1 year than the group without prostatitis [28]. However, these results were again confounded by a higher rate of preoperative urethral catheterization in the group with prostatitis (24% vs 11%).…”
Section: Aurmentioning
confidence: 97%